Four operation modes of a pulse tube machine with a step piston compressor. (1st April 2016) - Zhu, Shaowei
Abstract: An inertance tube pulse tube refrigerator with a step piston compressor is a reversible refrigerator which means that it can be operated as a refrigerator, a cold engine, a heat engine, and a heat pump. We call it as a pulse tube machine. In this paper, a numerical simulation is conducted on an inertance tube pulse tube machine with a step piston compressor. The result shows that the pulse tube machine can work as a refrigerator, a cold engine, a heat engine, and a heat pump, depending on the swept volume ratio of the step piston compressor. Highlights: A step piston type pulse tube machine is discussed by numerical simulation. It can work as refrigerator, cold engine, heat engine, and heat pump modes. Its operation mode depends on the critical swept volume ratio. High efficiency range is near the critical swept volume ratio.